Emotional Intelligence and Leadership Effectiveness among Local Leaders in Kisii County - Atege, Edwin Orina; Juma, Dennis (Human Resource and Leadership Journal, 2025)
Purpose: The objective of this study was to examine the role of EI on leadership effectiveness. Specifically, the study sought to determine the effect of self-regulation, self-awareness, self-motivation and social skills. The study was guided by emotional intelligence theory, transformational theory and social learning theory. Methodology: The study used the survey research design. The target population was 124 chiefs in Kisii County. A census of all the chiefs was done to obtain a population for the study. Purposive sampling was used to select the respondents. Data was collected using questionnaires and analyzed using descriptive statistics that included percentage, mean and standard deviation. To establish the relationship between the variables, regression analysis was used. Findings: The results indicated that emotional intelligence has significant positive effect on leadership effectiveness. This was supported by B-coefficients self-awareness β1=-0.253, P=0.000; self-regulation β2=0.194, P=0.000 self-motivation; β3=0.306, P=0.000; social skills β4=0.189, P=0.001. The coefficient of determination (R2) was 0.662, P=0.000 and this shows that 66.2% of the variations in leadership effectiveness can be explained by the independent variables. Unique Contribution to Theory, Policy and Practice: This study uniquely contributes to theory by enriching the understanding of emotional intelligence as a critical predictor of leadership effectiveness in decentralized governance. It informs policy by emphasizing the need to integrate emotional intelligence training into leadership development frameworks for local administrators. Practically, it guides leadership practice by highlighting specific emotional competencies that enhance decision-making, self-awareness, and interpersonal relations among local leaders in Kisii County, thereby improving governance outcomes.